Efficacy of Single Time Ultrasound Guided Needle Aspiration in Treating Breast Abscess - Uzair Ahmed Qureshi, Saad Arshad, Muhammad Azam Tayyab, Gul Rukh Khawar, Abdur Rehman Alvi, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Antibiotics administration, incision and drainage, and ultrasound-guided needle aspiration are the most commonly used treatment options for breast abscesses. Ultrasound guided needle aspiration has the advantage of early healing and fewer complications. The objective of the current study was to find out the efficacy of single time ultrasound guided needle aspiration in treating breast abscess. Material and Methods: A case series study was carried out at Surgery Department, DHQ Hospital Gujranwala from 05/08/2017 to 04/02/2018. This research included 90 female patients aged between 18-45 years presenting in surgical outdoor with breast abscess. Ultrasound guided aspiration of the abscess was performed using aseptic technique and 14 gauge needle and broad spectrum antibiotics were given for 1 week after the procedure. Follow-up of patients was done after 30 days and ultrasound (showing total absence or presence of less than 5ml collection) was performed to confirm the efficacy of the procedure. Results: Mean age of the study participants was 31.16±6.64 years. The size of abscess ranged from 0.5 cm to 4.9 cm with a mean of 3.34±1.09 cm. Majority (64.4%) of the abscesses were larger than 3 cm. 46.7% patients were lactating while 53.3% patients were non-lactating. The volume of pus aspirated ranged from 5 ml to 111 ml with a mean of 62.20±29.42 ml. Majority (57.8%) of the abscesses had pus in the range of 50-100 ml followed by less than 50 ml (33.3%) and more than 100 ml (8.9%). A single ultrasound guided needle aspiration of breast abscess resulted in resolution of abscess in 82.2% patients. There was no significant variation in the efficacy of single time ultrasound guided needle aspiration of breast abscess across various groups based on age, size, lactation status and volume of pus. Conclusion: A single time ultrasound guided needle aspiration of breast abscess resulted in abscess resolution in 82.2% patients regardless of age of patients, lactation status, size of abscess and volume of pus aspirated which advocate its regular utilization in daily practice.